1996
DOI: 10.1088/0953-4075/29/14/024
|View full text |Cite
|
Sign up to set email alerts
|

Many-body calculations of positron scattering and annihilation from noble-gas atoms

Abstract: Abstract. We have applied many-body theory methods to study the interaction of low-energy positrons with noble-gas atoms. The positron-atom correlation potential includes explicitly the contribution from the target polarization by the positron and that from the virtual positronium (Ps) formation. It is demonstrated that the correlations and Ps formation (or tunnelling of electrons from the atom to the positron) create virtual levels in the positron-atom system. The existence of the virtual levels strongly infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
166
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(187 citation statements)
references
References 54 publications
18
166
1
2
Order By: Relevance
“…The mean value of r 2 is taken to be that of the positron for e Be and e Mg. For e He 3 S e , e Li, and e Na; hr 2 i is taken to be the mean of the electron and positron expectation values. the annihilation rate [34,35]. These positron-molecule bound states are likely to be similar in character to e Be, with postulated energies ranging from 5 10 ÿ4 to 5 10 ÿ3 hartree [34].…”
Section: Prl 94 033402 (2005) P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 95%
“…The mean value of r 2 is taken to be that of the positron for e Be and e Mg. For e He 3 S e , e Li, and e Na; hr 2 i is taken to be the mean of the electron and positron expectation values. the annihilation rate [34,35]. These positron-molecule bound states are likely to be similar in character to e Be, with postulated energies ranging from 5 10 ÿ4 to 5 10 ÿ3 hartree [34].…”
Section: Prl 94 033402 (2005) P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 95%
“…Research on atomic systems [9,20,[29][30][31] has shown that there is a dynamical connection between the size of the lowenergy phase shifts and the annihilation parameter. An attractive interaction leads to the amplitude of the wave function being larger close to the origin, and therefore can be expected to increase the annihilation parameter.…”
Section: Heuristic Description Of Phase-shift Behaviormentioning
confidence: 99%
“…This effect will be called the clustering effect and is well known in condensed-matter systems [33,34], positron-atom scattering systems [20,29,30,36], and positron-atom bound states [19,37].…”
Section: On the Nature Of Annihilation Enhancementmentioning
confidence: 99%
“…One-electron HartreeFock with random phase approximations [12] was employed to calculate the scattering cross section of positrons on noble gas and alkali atoms. The many-body theory methods [13] are applied to study the interaction of low-energy positrons with Xe atoms which described by means of a non-local energy dependent-correlation potential. The polarized or- * Electronic address: mabdelmageed@hotmail.com bital method [14] is applied to calculate the elastic scattering cross section and annihilation rates of low energy positrons on xenon atoms below the positronuim formation threshold.…”
Section: Introductionmentioning
confidence: 99%